2023
DOI: 10.1002/alr.23261
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for decreased baseline quality of life in patients with sinonasal malignancies

Cara M. Fleseriu,
Daniel M. Beswick,
Sabrina L. Maoz
et al.

Abstract: BackgroundThe impact of sinonasal malignancies (SNMs) on quality of life (QOL) at presentation is poorly understood. The Sinonasal Outcome Test (SNOT‐22) and University of Washington Quality of Life (UWQOL) are validated QOL instruments with distinctive subdomains. This study aims to identify factors impacting pretreatment QOL in SNM patients to personalize multidisciplinary management and counseling.MethodsPatients with previously untreated SNMs were prospectively enrolled (2015–2022) in a multicenter observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In our group's recent report, patients with SNM presented with globally worsened sinonasal QOL at baseline. 20,39 SNOT-22 scores were elevated at the time of diagnosis, but improved gradually over the post-treatment period, surpassing the MCID threshold of −8.9 between 2 and 5 years after baseline. 20,39 In the present study of sinonasal subdomain QOL, we observed that the reductions in sinonasal QOL were primarily attributable to improvements in rhinologic, extra-nasal, sleep and psychological subdomains.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our group's recent report, patients with SNM presented with globally worsened sinonasal QOL at baseline. 20,39 SNOT-22 scores were elevated at the time of diagnosis, but improved gradually over the post-treatment period, surpassing the MCID threshold of −8.9 between 2 and 5 years after baseline. 20,39 In the present study of sinonasal subdomain QOL, we observed that the reductions in sinonasal QOL were primarily attributable to improvements in rhinologic, extra-nasal, sleep and psychological subdomains.…”
Section: Discussionmentioning
confidence: 91%
“…20,39 SNOT-22 scores were elevated at the time of diagnosis, but improved gradually over the post-treatment period, surpassing the MCID threshold of −8.9 between 2 and 5 years after baseline. 20,39 In the present study of sinonasal subdomain QOL, we observed that the reductions in sinonasal QOL were primarily attributable to improvements in rhinologic, extra-nasal, sleep and psychological subdomains. On subanalysis of our cohort of patients with complete follow-up data (the "Complete" subcohort), both the rhinologic and extra-nasal subdomains showed statistically significant improvement but fell short of MCID thresholds.…”
Section: Discussionmentioning
confidence: 91%
“…Two recent studies also identified gender differences in QoL after skull base surgery. 9,10 The first study by Buchlak et al in 2022 found that low preoperative QoL is negatively associated with female gender in endoscopic pituitary surgery using the anterior skull base surgery (ASBS) questionnaire. Another study by Fleseriu et al in 2023 also found worse baseline rhinologic QoL in female patients using the SNOT-22 rhinologic domain in patients with sinonasal malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, OE carries significant morbidity and decreased quality of life. [9][10][11] Recently, multimodal therapies to achieve improved survival without OE has been investigated. One approach is the use of induction chemotherapy (IC), a promising treatment modality that may allow for OP treatment without compromising patient oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%